PENGARUH KEAHLIAN AUDITOR TERHADAP AUDIT JUDGEMENT (STUDI EMPIRIS DI KAP DI SURABAYA) - Mohammad Fairuz Rizal; Ardhi Islamudin (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
The role of public accountants is highly vital in maintaining public trust through audited financial statements as a basis for decision-making. The most significant factor influencing the quality of this audit judgment is auditor expertise, which is formed from a combination of knowledge, experience, and training. Therefore, this study aims to examine and analyze the positive and significant effect of auditor expertise on audit judgment at Public Accounting Firms (KAP) in Surabaya. This study employs a quantitative approach by distributing questionnaires directly to respondents to obtain primary data. The research population includes 54 KAPs in Surabaya. Sampling was conducted using a purposive sampling method with specific criteria, namely auditors with a minimum of one year of work experience. Data analysis was performed using simple linear regression and t-tests. The research results definitively prove that auditor expertise has a positive and significant effect on the quality of audit judgment. This finding is supported by a significance value of <0.001 and a t-count of 28.140, which exceeds the t-table limit. These empirical results align with the Cognitive Theory of Multimedia Learning (CTML), where adequate auditor expertise can significantly reduce cognitive load through automated information processing, thereby producing more rational and precise judgments. As a practical implication, KAP leaders in Surabaya are strongly advised to continuously prioritize human resource development strategies through sustainable professional training programs. Increasing practical experience and competence is crucial for auditors to avoid audit failures. Ultimately, this will have a direct impact on maintaining the firm's reputation and increasing stakeholder trust in the credibility of published audit opinions.